Kinematic variables for upper limb rehabilitation robot and correlations with clinical scales: A review - Sulaiman Mazlan; Hisyam Abdul Rahman; Yeong Che Fai; Babul Salam Ksm Kader Ibrahim; Muhamad Saif Huq (Institute of Advanced Engineering and Science, 2020)
The paper presents a comprehensive review carried out to identify the kinematic variables used in upper body rehabilitation assisted by robotic devices to assess the motor impairment of stroke patients and investigates the correlation between the kinematic variables and the clinical scales. Twenty-nine kinematic variables have been studied from twenty-eight articles involving 738 subacute or chronic stroke patients. The movement of speed, distance, accuracy, peak speed, peak speed ratio and number of peak speed were found to be the most frequently used kinematic variables in the aforementioned studies. Seven out of twenty-eight included articles examined the correlations between the kinematic variables used with the clinical scales. Some kinematic variables seem to have a strong correlation with the clinical scales but most of the kinematic variables have a moderate or weak correlation value. The important kinematic variables for evaluating the motor performance during rehabilitation assisted by robotic devices have been discussed. A suitable selected set of kinematic variables and clinical scale can potentially enhance the correlation value, at the same time can predict the clinical score evaluated by physiotherapist during the rehabilitation program with a high degree of accuracy.